Escola e instituição de acolhimento: articulações necessárias para a acessibilidade de estudantes com deficiência - Teixeira, Carolina Terribile (2016)
This research part of concerns about accessibility in education and the articulation between school and host institution.This research addresses handicapped students experiencing residential care and the necessary articulations between the school and the host institution in order to promote accessibility for them. Therefore, the guiding question of the study was: How does the articulation between school and host institution happen in relation to handicapped children and teenagers accessibility? To answer the question, the general objective set out was to investigate how the actions concerning the accessibility for handicapped children and teenagers are constituted in the school and host institution practices. To reach the general objective, the specific ones were: to verify which understanding of accessibility the professionals who work both at school and host institution have; to identify how the social mother s monitoring, who is responsible for handicapped children and teenagers in school, is; and to analyze how the relations between the school and the host institution are established for accessibility promotion. The research took place in a host institution, a school and a special school. The participants were: the Technical Team and the Social Mother s of the host institution; and the directors of the schools. This study is qualitative research of the case study type and, for data collection, semi-structured interviews and observations were carried out. With the accomplishment of the research, it was found that, even with the advances in public policies that deal with the rights of these children and teenagers, they still face barriers on a daily basis. In addition, it was verified that the understanding about accessibility remains without profound clarification, causing fuzziness with the term access and usually being associated with architectural structures on the reports. Also, it was noticed that the school monitoring by the social mother happens through meetings, talks and notes and that she has difficulties to follow all of them in their tasks at home. Concerning the relations between school and host institution, the participants emphasized them as being positive. However, it was detected that the articulation for accessibility is still incipient and needs mobilizations for its implementation. Therefore, we believe that the relevance of this research lies on giving opportunity the comprehension of the reality found and experienced at schools and host institutions that assist handicapped children and teenagers. Because this is an underexplored subject, we highlight its contribution to the academic sphere.